The Implementation of Science, Technology, Environmental and Society (STML) Learning on the Student's Creativity in Handling and Management of Waste at SD Negeri Doplang 01 - Sumaliyah Sumaliyah (UM Purwokerto Press, 2023)
Independent Curriculum content is expected that elementary school students will care more about the environment. The students' characteristics at the elementary school level are still unaware of the cleanliness, the negative impact, and the dangers of waste, so SD Negeri Doplang 01 implements learning that can manage waste optimally. The study aimed to determine the impact of learning Science, Technology, Society and Environment (STML) on students' waste handling and management creativity at SD Negeri Doplang 01. The method used was an experiment using a quasi-experimental design in the form of a Time Series Design that the group used for research was selected randomly. This research design employed one group only, so it does not require a control group. The population was students of class IV semester 2 SD Negeri Doplang 01, and the sample was obtained through a saturated sample or census. Data collection techniques were tests and documentation. The test method was a creativity questionnaire by a Likert scale to measure students' creativity. This study utilized a t-test analysis method assisted by SPSS 25. From the results of data analysis, the average pretest value was 309.7 and the average posttest value was 354.25. The results of statistical analysis using the t-test through SPSS 25 obtained Sig (2-tailed) 0.000 with a significance level of ?=0.05. The study's conclusion states that there are differences in learning using Science, Technology, Society, and the Environment (STML) on the creativity of handling and managing waste in grade IV students at SD Negeri Doplang 01.